KONSTRUKSI SEKSUALITAS PEREMPUAN DALAM BERITA PEMERKOSAAN DI TEKS MEDIA DARING - Daniel Susilo; Eben Haezer (Universitas Gadjah Mada, 2017)
Since 2010, Indonesian media have a significant change in a medium of distribution the message. Slow but sure, online news media became the main favourite choose for accessing the information by Indonesian people. In the same time, rape news in the yellow newspaper became digitalized and moved to online news media. This study uses critical discourse analysis by Van Dijk to show how the media construct the women sexuality in the press text. Researcher uses JPNN.com as the object of the research. Item to be observed are thematic, schematically, semantic, syntactic, stylistic and rhetorical. Results of this research indicates women sexuality as commodity might by men. Besides, the online news site simultaneous reinforce the view